Mapeo de posibles instrumentos de Tecnologías de Información y Comunicaciones para la producción de quinua del altiplano boliviano - Sheila C. Muriel H. (Institute for Advanced Development Studies (INESAD), 2022)
– Information and Communications Technologies (ICT) for the agriculture sector present diverse characteristics and serve for multiple purposes; information systems, wireless sensors, drones, etc. These are used for the care of resources, such as soil and water, for improving and monitoring crops, and for risk prevention, among others. From this wide spectrum of possibilities, I map possible ICT tools for quinoa producers in the Bolivian highlands; which is a subset of tools framed according to: ICT needs and skills of the producers, the feasibility of their implementation, availability, etc. In order to recognize the viability of these tools, I carry out a sweep of information on the growing technology and/or in use worldwide, until reaching the sector of interest considering its availability at a regional level; and respecting the way of cultivation of producers and not affecting negatively the organic quality of quinoa to preserve its mention of origin, among others. In the schematization of the mapping, I consider the Supply Chain Process with its basic components: supplies, production and distribution; seeking to have the perspective of a system, not only of its components, but also the interaction between them and the influences of their environment. The presented tools can be summarized under two perspectives: tools that manage information (such as information systems) and tools that collect information (such as drones, sensors and Radio Frequency Identification technology -RFID-).
Keywords: O30; O33; Q16; 330; Information and Communication Technologies (TIC); agrotech; agritech; agtech; crop monitoring; Information Systems